2021
DOI: 10.1002/14651858.cd013281.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing type 2 diabetes in adults with mental disorders in low- and middle-income countries

Abstract: This is a repository copy of Interventions for preventing type 2 diabetes in adults with mental disorders in low and middle income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 159 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5] This raises an obvious question regarding potential prevention of DM in this at-risk group of patients. While there has been very little evidence supporting specific pharmacological and non-pharmacological interventions to reduce obesity and the risk of DM in the context of bipolar disorder, 48,49 a recent study among patients with bipolar disorder and insulin resistance suggests that metformin may be beneficial in this regard. 38 Specifically, in the randomized controlled trial by Calkin and colleagues, 14 weeks of daily treatment with 2 mg metformin led to 11 of 20 participants no longer meeting criteria for insulin resistance, compared with only 1 of 25 participants receiving placebo.…”
Section: Cumulative Dose-response-like Associationsmentioning
confidence: 99%
“…[1][2][3][4][5] This raises an obvious question regarding potential prevention of DM in this at-risk group of patients. While there has been very little evidence supporting specific pharmacological and non-pharmacological interventions to reduce obesity and the risk of DM in the context of bipolar disorder, 48,49 a recent study among patients with bipolar disorder and insulin resistance suggests that metformin may be beneficial in this regard. 38 Specifically, in the randomized controlled trial by Calkin and colleagues, 14 weeks of daily treatment with 2 mg metformin led to 11 of 20 participants no longer meeting criteria for insulin resistance, compared with only 1 of 25 participants receiving placebo.…”
Section: Cumulative Dose-response-like Associationsmentioning
confidence: 99%
“…However, the usefulness of educational programs such as STEPWISE, a theory-based group education in the field of health-promoting lifestyle, which at 12 months demonstrated neither clinical nor financial benefits for patients with schizophrenia [49], is questioned. Despite the presence of controversy related to the difference in the risk of developing carbohydrate metabolism disorders between patients using typical and atypical antipsychotics [50], it should be borne in mind that sertinodl, zotepine, clozapine, and olanzapine are associated with a high risk of weight gain, while amisulpiride, asenapine, quetiapine, risperidone, paliperidone, and iloperidone -with moderate, and aripirazole, brexiprazole, cariprazole, and ziprasidone --with low risk. Therefore, taking into account also the aforementioned diabetogenic potential, a switch to another antipsychotic medication is suggested, if possible [51].…”
Section: Reviewmentioning
confidence: 99%
“…The latest published reviews assessing different metabolic aspects have mixed results. A recent Cochrane review evaluating interventions to prevent type 2 diabetes in patients with SMD in low- and middle-income countries was inconclusive [ 14 ]. A meta-analysis by Naslund et al of lifestyle weight loss interventions for overweight and obesity in SMD patients, concluded that such interventions were effective, especially those lasting longer than 12 months, which have a clinically significant ≥ 5% weight loss at follow-up [ 15 ].…”
Section: Discussionmentioning
confidence: 99%